C03 FAN1 coding variants identified in individuals with Huntington's disease implicate its nuclease activity and dna binding in age at onset. (12th September 2022) - Binda, Caroline S; McAllister, Branduff; Menzies, Georgina; Edwards, Gareth; Davies, James; Jones, Lesley; Massey, Thomas H
Abstract : Background: Age at onset of motor symptoms in Huntington's disease (HD) is driven by HTT CAG repeat length but modified by other genes. FAN1 is a candidate modifier gene identified in previous genome-wide association studies associated with altered HD onset or severity. FAN1 is a structure-specific 5′ exo/endo-nuclease involved in interstrand crosslink (ICL) repair. Aims: We aimed to identify rare coding variants in FAN1 associated with clinical effect in individuals with HD and elucidate the biochemical mechanisms by which FAN1 modifies age at onset. Methods/Techniques: We used exome sequencing of 683 individuals with HD with extremes of onset or phenotype relative to CAG length. We applied molecular dynamics modelling to prioritise FAN1 coding variants for downstream biochemical studies. We assessed ICL-repair efficacy in lymphoblastoid cell lines derived from HD patients heterozygous for FAN1 variants. We assayed endonuclease activities and DNA-binding capacities of FAN1 proteins on canonical FAN1 substrates. Results/Outcome: We discovered damaging coding variants in FAN1 that clustered in its DNA-binding and nuclease domains and were associated predominantly with earlier-onset HD. We found that lymphoblastoid cell lines derived from HD patients heterozygous for the previously identified early-associated R507H variant were more sensitive to mitomycin C than its matched counterpart and showed significantly lower IC50 means. Nuclease activities of purified FAN1 variant proteins in vitro correlated with residual age at motor onset of HD. Conclusions: Heterozygous damaging coding variants in FAN1 with lower nuclease activities are associated with earlier onset of HD after accounting for CAG length.